Production of zeolites from oil palm ash - Attiyah, Ariffin (2010)
In this research, the ability of oil palm ash to produces value added product such as zeolites is studied. Characterization of oil palm ash from one of the palm oil plantation in Malaysia has been carried out and used for the production of zeolites. The production of zeolites from oil palm ash appears to be one of the alternatives in the utilization of waste materials. The method used to produce zeolites is alkaline hydrothermal treatment .The characterization analysis of oil palm ash and zeolites are diffraction pattern, morphological structure, and chemical composition. The characterization equipment involved is X-Ray diffraction (XRD), scanning electron microscopy (SEM) and X-Ray fluorescence (XRF). The experiment is conducted at laboratory of FKKSA UMP while some characterization analysis is carried out at laboratory of environmental analysis at UTHM. From the mineralogical studies carried out, it was found that silica and alumina were the major component of oil palm ash and zeolites. The maximum condition for production of zeolites is at 1:3 NaOH/OPA ratio, hydrothermal temperature 80°C and hydrothermal time 6 hour. The present result is very much useful in opening up way to produce zeolites at low cost with useful application.